Knowledge, Attitudes and Practices about Cardiovascular Diseases among Adult Patients Attending Public Health Centers in Kigali city, Rwanda - Leonard Ntwari Nyagasare; Emmanuel Muvandimwe; Micheal Habtu; Erigene Rutayisire (Journal of Public Health International, 2022)
In Rwanda, CVDs accounts around 14% of all death. Studies on knowledge, attitude, and practice (KAP) would be of great value in helping public health professionals develop targeted programs and measure the effectiveness of interventional programs. The main objective of this study was to analyze the KAP about CVDs among adult patients attending public health centers located in the City of Kigali, Rwanda. A total of 384 adult patients were enrolled in this study. A structured questionnaire was used. Data entry and analysis was done using SPSS version 21. Findings were presented as frequencies and percentages in tables. For determining the KAP-levels, the overall scores were determined for each respondent by adding up the scores through the KAP-related questions. The mean age was 36.4 years, primary school (57.3%), married (62.8%), self-employed (40.9%), and females predominated (61.5%). The knowledge mean score was 14.2 and 76% had high level of knowledge of CVD risks and prevention. The average attitude score for all respondents was 17.6 and 22.9% of the respondents showed negative attitude towards CVDs prevention. Research findings revealed that 36.5 % were not practicing physical activity and exercise. The mean practice score for all respondents was 3.9 and 70% of respondents had negative practice towards CVDs prevention. Poor CVDs prevention practices were observed among the study participants. Therefore, it is necessary to establish more effective educational interventions intended to promote positive health behaviors related CVD prevention
Keywords: Cardiovascular disease